Self-assembled nanocomposite of organic-inorganic hybrid: 2,4-Dichlorophenoxyacetate in Zn-Al Hydrotalcite-like layers - Hussein, Mohd Zobir Bin; Amin, Junainah Bt Mohd; Zainal, Zulkarnain; Yahaya, Asmah Hj (American Scientific Publishers, 2002)
Hydrotalcite-like inorganic layers of Zn-Al, a host containing an organic moiety, 2,4-dichlorophenoxyacetate, as a guest, was prepared by the spontaneous self-assembly method from an aqueous solution for the formation of a new layered organic-inorganic hybrid nanocomposite material. In this synthesis, the host- and guest-forming species were simultaneously included in the mother liquor, aged, and separated. Various Zn/Al ratios (R = 2, 3, and 4), concentrations of 2,4-dichlorophenoxyacetic acid (0.03-0.1 M), and pH (7 and 10) were studied to optimize the formation of the layered nanocomposite. It was found that the optimum conditions for the formation of the nanocomposite were R = 4, pH 7, and concentration of 2,4-dichlorophenoxyacetic acid = 0.08 M. X-ray diffraction shows that this sample affords a nanolayered structure with a basal spacing of 24.6 Å.